OLD OBSTACLES AND NEW OPPORTUNITIES IN REGIONAL COOPERATION OF LOCAL GOVERNMENTS - Ferenc SZABÓ (Management & Marketing)
Abstract:The accession of Hungary to the European Union created vast opportunitiesfor the development of infrastructure in the area of environmental protection.But the financial resources almost always depend on the availability of somekind of regional cooperation or territorial integration. In my paper, I study theexperiences gained regarding the establishment and operation of regionalcooperation; the reasons of the difficulties of operation during short-termcooperation and the future possibilities for cooperation in the long run on thebasis of a quantitative analysis of the „Szeged Regional Waste ManagementProgramme” ISPA/Cohesion Found project. It was to establish a projectregion of 250 thousand inhabitants, which region is the beneficiary of theEuropean Union support. In order to analyse the reasons of the defaults ofoperation, I proposed a hypothesis based on the interviews conducted withproject managers and experts involved in the project studied. I conducted aquestionnaire survey in order to check the validity of the hypothesis by way ofa quantitative method. The analyses of the questionnaires of therepresentatives of the 32 municipalities appeared to partly confirm thehypothesis, in other respects they extended beyond the statements of thehypothesis. Although past traditions of natural cooperation based on mutualbenefit had died out during the forty years of socialism, European Unionprojects, however, forced new types of regional cooperation, i.e., projectregions, to develop shortly after the change of the regime.